Inpatient management and post-discharge outcomes of hyperkalemia. Issue 4 (8th August 2021) - Davis, Jill; Israni, Rubeen; Mu, Fan; Cook, Erin E.; Szerlip, Harold; Uwaifo, Gabriel; Fonseca, Vivian; Betts, Keith A.
ABSTRACT: Objectives: Patients with hyperkalemia are commonly treated in the inpatient setting; however, real-world evidence is limited. The purpose of this study was to describe the inpatient management and post-discharge outcomes among patients with hyperkalemia. Methods: Electronic medical record data (2012–2018) were used to analyze US adult patients with an inpatient stay with hyperkalemia (≥1 potassium value >5.0mEq/L). Patient characteristics, treatments, and monitoring six months prior to and during the inpatient stay, and hyperkalemia recurrence and inpatient readmissions post-discharge were summarized and compared among patients with mild (>5.0–5.5mEq/L), moderate (>5.5–6.0), and severe (>6.0) hyperkalemia. Results: Of the 21, 793 patients, 69.2% had mild, 19.0% had moderate, and 11.8% had severe hyperkalemia during inpatient care. The most common inpatient treatments were temporizing agents (mild: 28.9%; moderate: 46.0%; severe: 73.0%), diuretics (32.7%; 37.1%; 34.6%), and sodium-polystyrene sulfonate (11.7%; 27.8%; 45.3%). Almost no patients (0.1%) received a potassium binder at discharge. Most patients (86.8%) had their potassium levels return to ≤5.0mEq/L during the inpatient stay. Death during the inpatient stay occurred in 12.3% of mild, 15.5% of moderate, and 19.5% of severe hyperkalemic patients. Within 30 days of discharge, hyperkalemia recurred in 13.3%, 15.4%, and 18.4% of patients with mild, moderate, and severe hyperkalemia, respectively. Additionally, 19.7%, 21.5%, and 19.6% of patients were readmitted to inpatient care within 30 days post-discharge. Conclusion: Among patients with hyperkalemia in the inpatient setting, treatment and normalization of serum potassium levels were common. However, death, readmission, and hyperkalemia recurrence were also fairly common across all cohorts. Future studies examining measures to reduce inpatient death, readmission, and hyperkalemia recurrence among patients with hyperkalemia in inpatient care are warranted.